2017
DOI: 10.1155/2017/6158468
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sevoflurane Exposure Causes Abnormal Development of Fetal Prefrontal Cortex and Induces Cognitive Dysfunction in Offspring

Abstract: Maternal sevoflurane exposure during pregnancy is associated with increased risk for behavioral deficits in offspring. Several studies indicated that neurogenesis abnormality may be responsible for the sevoflurane-induced neurotoxicity, but the concrete impact of sevoflurane on fetal brain development remains poorly understood. We aimed to investigate whether maternal sevoflurane exposure caused learning and memory impairment in offspring through inducing abnormal development of the fetal prefrontal cortex (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Nevertheless, impairment of layer 6 neurogenesis has been linked to learning/memory deficit. For instance, sevoflurane exposure of pregnant mice causes layer 6 neurogenesis defect and learning/memory abnormality ( 30 ). In addition, the layer 6 marker Tbr1 is essential for specifying layer 6 identity ( 31 ), and its heterozygous variants have been found in patients with autism spectrum disorder ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, impairment of layer 6 neurogenesis has been linked to learning/memory deficit. For instance, sevoflurane exposure of pregnant mice causes layer 6 neurogenesis defect and learning/memory abnormality ( 30 ). In addition, the layer 6 marker Tbr1 is essential for specifying layer 6 identity ( 31 ), and its heterozygous variants have been found in patients with autism spectrum disorder ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mPFC development is a continuous process and retains its neuroplasticity throughout the life 24 . Thus, sevoflurane could induce neurodevelopmental diseases by regulating synaptogenesis and synaptic development in the mPFC 36 , which suggests that mPFC neurons are vulnerable to sevoflurane-induced neurotoxicity. Indeed, our study found that neonatal exposure to sevoflurane-induced ADHD-like impulsive behavior at the adult stage through over-activating the mPFC excitatory neurons ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine anaesthesia interrupts the transfer of information between cortical areas in Rhesus monkeys and humans [43,44]. Prenatal anaesthesia, with ketamine or sevoflurane, causes neuronal loss and dysplasia of pyramidal neurons in the prefrontal cortex of rat pups [45,46]. Stimulation of the same cells alleviates ADHD signs [33].…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…Clinical studies [7][8][9][10][11][12][13][14][15] Animal studies [16][17][18][19][20] Neural molecular mechanisms Dopamine receptor [6,[21][22][23][24][25][26][27][28] N-methyl-D-aspartic acid receptor [29][30][31][32][33][34][35][36] Brain-derived neurotrophic factor [37][38][39][40][41] Neural network mechanisms Prefrontal cortex [33,[42][43][44][45][46][47][48][49][50] Synaptogenesis [7,33,[47][48][49]…”
Section: Content Referencesmentioning
confidence: 99%